In vitro antimicrobial activity of extracts of some plant species used in the management of HIV/AIDS in Tanzania - Mpinda, Cyprian Beda; Meyer, Debra; Lyantagaye, Sylvester Leonard (Tanzania Journal of Science, 2021)
Six plants species (Harungana madagascariensis, Sapium ellipticum, Teclea nobilis, Pseudospondias microcarpa, Rauvolfia vomitoria and Psorospermum febrifugum) which are used in managing HIV/AIDS in Bukoba, Tanzania were screened for their antimicrobial effect on the selected representatives of infectious bacterial and fungal species. Gram-positive bacteria Streptococcus lactis, Gram-negative bacteria Klebsiella pneumoniae and a fungus Candida albicans were tested for their sensitivity to the treatment with selected plants extracts using disc diffusion and broth dilution techniques. Extracts of S. ellipticum, P. febrifegum and P. microcarpa demonstrated growth inhibition of S. lactis with the MIC ranging from 3.2 to 100 mg/ml. The extracts of S. ellipticum, P. febrifegum and T. nobilis demonstrated growth inhibition of K. pneumonia with the MIC ranging from 6.3 to 25 mg/ml. On the other hand, extracts of H. madagascariensis, P. microcarpa and R. vomitoria inhibited growth of C. albicans with the MIC ranging from 12.5 to 50 mg/ml. These results are very promising towards discovery of new antimicrobial drugs especially against neglected S. lactis, K. pneumoniae and invasive Candida infections and could explain the routine use of the plants’ infusions in traditional medicines in Bukoba against HIV/AIDS related illnesses. Keywords: Bukoba Tanzania, HIV/AIDS, opportunistic infections, plant extracts, traditional medicine